Effectiveness and Safety of Reirradiation With Stereotactic Ablative Radiotherapy of Lung Cancer After a First Course of Thoracic Radiation: A Meta-analysis - Viani, Gustavo A.; Arruda, Caio V. [UNESP]; De Fendi, Ligia I. (Wolters Kluwer, 2020)
OBJECTIVE: The effectiveness and safety of reirradiation with stereotactic ablative radiotherapy (re-SABR) in patients with recurrence after a previous course of radiation are limited to small series. We carried out a meta-analysis to summarize existing data and identify trends in overall survival (OS), local control (LC), and toxicity after re-SABR in patients with recurrence of lung cancer. MATERIALS AND METHODS: Eligible studies were identified on Medline, Embase, the Cochrane Library, and the proceedings of annual meetings through June 2019. We followed the PRISMA and MOOSE guidelines. A meta-regression analysis was carried out to assess whether there is a relationship between moderator variables and outcomes. A P-value<0.05 was considered significant. RESULTS: Twenty observational studies with a total of 595 patients treated were included. The 2-year OS and LC were 0.54 (95% confidence interval [CI]: 0.48-0.61) and 0.73 (95% CI: 0.66-0.80), respectively. The rate of any toxicity grade ≥3 was 0.098 (95% CI: 0.06-13.6), with 9 grade 5 toxicity (1.5%). In the meta-regression, the re-SABR dose (P=0.028), tumor size (P=0.031), and time to recurrence (P=0.018) showed an association with survival. For LC, the re-SABR dose (P=0.034) and tumor size (P=0.040) were statistically significant. Any toxicity grade ≥3 showed a relationship with the cumulative dose (P=0.024). Cumulative dose ≤145 versus >145 Gy2 had 3% versus 15% (P=0.013) of any grade ≥3 toxicity. CONCLUSIONS: Re-SABR produces satisfactory LC and OS rates with an acceptable rate of toxicity. The balancing between the re-SABR dose and the tumor location has the potential to reduce severe and fatal toxicity.